دور البيئة في تشكيل العمارة الصحراوية - ورغ, كامل سعيد; ورغ, هبه كامل (مجلة شروس العلمية, 2023)
Keywords: Architecture -- Mzab

André Ravéreau, lezioni a confronto : oltre i confini del M'Zab - Ruggeri, Daniela (Rassegna di architettura e urbanistica, 2023)
Keywords: Architecture -- Mzab

Étienne Chouinard revient sur l’architecture du Marais breton - Pointeau, Eléonore (Ouest-France, 2023)
Keywords: Architecture -- Mzab

A Strategy to Improve Comfort Level and Optimize the Thermal Behavior of the Building: Learning from M’zab Architecture - Messaitfa, Abdelwahab; Bencherif, Meriama (Prostor, 2023)
Due to centuries of rich experience, vernacular architecture offers significant lessons on sustainable building practices. This style competes exceptionally well with contemporary designs because of its efficiency, adept functionality, environmental compatibility, and harmonious relationship with human societies. The M'zab Valley in Ghardaia, Algeria, deserves to be classified as a World Heritage Site because it features original vernacular architecture that expresses smart building concepts while blending seamlessly into natural landscapes. In this paper, we validate the hypothesis that traditional Ghardaia housing in the Ksour reflects high energy efficiency and low reliance on active heating and cooling. We shall conduct a comparative study between a traditional dwelling belonging to vernacular architecture in the ancient Ksar Beni Isguen and a modern residence in Ksar Tafilelt. Through this comparison and simulation method, we seek to determine the most efficient architectural style in terms of energy use and the provision of thermal comfort in order to draw lessons and contribute to reducing the excessive consumption of non-renewable energies.
Keywords: Architecture -- Mzab

Dans la vallée du M’Zab, Ghardaïa la Pentapole - Heim, Jean-Pierre (Chroniques d‘architecture, 2023)
A Ghardaïa, dans le dédale des rues, les murs sans fenêtres laissent parfois apparaître un moucharabieh qui donne à voir la mosquée.
Keywords: Architecture -- Mzab